2014
DOI: 10.1097/mnm.0000000000000064
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography automatic exposure control techniques in 18F-FDG oncology PET-CT scanning

Abstract: CT AEC techniques from the three manufacturers yield significantly different tube current modulation patterns and hence deliver different doses and levels of image quality across a range of patient weights. Users should be aware of how their system works and of steps that could be taken to optimize imaging protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Noise constant systems such as GE and Toshiba result in a linear increase in CTDI vol with patient weight, but some ATCM systems intentionally decrease dose less for thinner adults . A comparison of CT scanners from three manufacturers showed that the Philips system had the least variation of DLP with patient weight, when compared with GE and Siemens . Some authors using GE scanners divide adult patients into weight categories …”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Noise constant systems such as GE and Toshiba result in a linear increase in CTDI vol with patient weight, but some ATCM systems intentionally decrease dose less for thinner adults . A comparison of CT scanners from three manufacturers showed that the Philips system had the least variation of DLP with patient weight, when compared with GE and Siemens . Some authors using GE scanners divide adult patients into weight categories …”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The AEC software used adjusts the tube current, which is proportional to the radiation exposure, so as to keep the image noise constant [ 17 ]. When using AEC, the radiation exposure depends on the type of AEC software, the parameters input into the software, and the direction of the localizer images [ 26 , 27 , 28 , 29 , 30 ]. There are facilities where AEC is not used for pediatric brain CT [ 10 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we do not know the impact of ATCM on nodule detection. ATCM is widely accepted as a suitable dose reduction method for DQ imaging [33][34][35][36][37] but despite the mA being limited to operate within upper and lower limits, 35 previous work 19 suggests the selection of "noise index" can be arbitrary and radiation dose may not be adequately optimised. Future work could assess nodule detection in DQ images acquired with and without ATCM using observer performance studies patterned on the current work.…”
Section: Discussionmentioning
confidence: 99%